Research on the Suitability of Wheat Flours for Lanzhou Ramen Noodles Making - WEI Yi-min; ZHAO Bo; YAN Jun-hui; ZHANG Lei; WANG Jiang-hua; ZHANG Ying-quan; ZHANG Bo; GUO Bo-li (Liang you shipin ke-ji, 2022)
Through the chain operation of the catering for the Lanzhou ramen noodles (hand-extended noodles) traditional noodle products become a model for brand management and a sample of product-driven catering industrial development. In the process of Lanzhou ramen chain operation, the supply of wheat flour suitable for making Lanzhou ramen and flour standardization are one of the main problems affecting business benefit and product quality. Milling companies need wheat ingredients and flour standards for making Lanzhou ramen. Flours of wheat varieties mainly cultivated in Guanzhong Plain were used as raw materials, the ramen was made by professional ramen masters. The ramen were evaluated by full-time food sensory evaluators, so wheat flour suitable for making Lanzhou ramen is screened out to provide a reference basis for the formulation of ramen standards. The results showed that in the sensory evaluation of ramen making process, the ramen master was more sensitive to “Extending force”, followed by “Degree of mixing and hardness of dough”. The wheat varieties of Xinong 583, Zhengmai 366, Weilong 169, Xinong 822, Bainong 207 and Zhongmai 578 as samples were more suitable for making Lanzhou ramen. It was found that the total sensory evaluation score of the ramen making process was closely related to the Alveograph parameters, while the total sensory evaluation score of the ramen product after cooking was closely related to the Extensograph parameters.